Optimasi pertumbuhan dan hasil tanaman pakcoy (Brassica rapa L.) melalui kombinasi dosis npk dan mikoriza - Aaz Azamudin Tifani; Miftah Dieni Sukmasari (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
This study aims to determine the effect of giving a different dose of NPK fertilizer with mycorrhizal inoculation on the growth and yield of pakcoy (Brassica rapa) plants. The research was carried out on a trial site of the Faculty of Agriculture, University of Majalengka using a non-factorial Group Random Design (RAK) with six NPK dose treatments and four replicas. The treatment consisted of A (0 g NPK + 8 g mycorrhiza), B (0.3 g NPK + 8 g mycorrhiza), C (0.6 g NPK + 8 g mycorrhiza), D (0.9 g NPK + 8 g mycorrhiza), E (1.25 g NPK + 8 g mycorrhiza), and F (1.50 g NPK + 8 g mycorrhiza) which were repeated four times. The observed parameters included plant height, number of leaves, root length, root volume, wet weight, and dry weight of the plant. The data from the study were analyzed using non-factorial RAK, if there was an influence on the treatment, followed by Duncan's follow-up analysis. The results showed that the combination of NPK and mycorrhizal fertilizers in general had a positive effect on vegetative growth and pakcoy plant yields. Treatment E (1.25 g NPK + 8 g mycorrhiza) gave the best results on most parameters, with higher increases in plant height, leaf count, and dry weight compared to other treatments. Thus, a dose of 1.25 g of NPK combined with 8 g of mycorrhizae is the optimal combination to support the sustainable growth and productivity of pakcoy.